Brexit and the UK Automotive Industry. (November 2017) - Bailey, David; De Propris, Lisa
The UK's automotive industry has been one of the 'star performers' of the UK economy in recent years – unlike most other manufacturing sectors. Output has increased by over 60 per cent since 2010 and there has been over £8 billion worth of investment in the industry in the past five years. The industry supports some 800, 000 jobs in the UK. It is seen as having benefitted from EU membership. So what might Brexit mean for the UK automotive sector, and its workers? This paper considers short-run impacts, before turning to the impact of uncertainty on foreign direct investment inflows and then the nature of a possible trading relationship. Some brief reflections on policy implications round off the paper.